Community-Based Financial Literacy Interventions for Empowering Micro, Small, and Medium Enterprises in Bangka Belitung - Kurniati, Ira; Rahmansyah, Nur; Damayanti, Indri; Putri, Lusiana; Sugiyono, Sugiyono; Aisha, Amelia Ayu Nur; Mardiani, Eri (Help: Journal of Community Service, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in driving economic growth and improving community welfare in Belitung Regency, Bangka Belitung Province. However, low levels of financial literacy remain a major obstacle for MSME actors, especially concerning business financial management, transaction recording, and effective financial decision-making. This community service activity adopted a Participatory Action Research (PAR) methodology, conducted as a collaborative training intervention involving the Association of Indonesian Accounting Lecturers (ADAI) and the Belitung Regency Government. The program was attended by 159 participants, including MSME partners, local residents, and regional leaders. The implementation consisted of four systematic stages namely preparation, counseling on simple financial management, interactive discussion and mentoring, and an evaluation utilizing pre-tests and post-tests. The intervention yielded a highly positive response and a measurable improvement in financial management knowledge. Evaluation results demonstrated that the average pre-test score of 44.25% increased sharply to 79.50% in the post-test. This reflects a significant average knowledge increase of 35.25%, successfully bridging the initial gap between passive theoretical knowledge and practical business application. The community-based education effectively raised MSME actors' awareness regarding the importance of financial literacy for making sound, sustainable business decisions. This enhanced capacity provides a strong foundation for better financial choices and supports local economic development. To maximize future community empowerment efforts, providing continuous post-training assistance and integrating user-friendly digital technology for financial record-keeping are highly recommended.